Ações encobertas - Pontes, Arménio Claro (2017)
The global and increasingly technological society requires the States to adopt security measures that can maintain the balance between the freedom, on the one hand, and the security and the respect for fundamental rights of a democratic state, on the other. A State can only achieve this aim if it has an effective judicial system and in particular a criminal procedure adequate to the new criminogenic realities. In this context, the national legislator has adopted, following other international legal systems, special means of obtaining proof more stringent of rights. Within those special means are included the covert actions, that, being a means to use sparingly, is a key element to fight against violent and highly organized crime. Therefore, the undercover agent, voluntary by nature, develops a set of activities that enables the investigation to use other means of taking evidence and/or probationary diligences itself, with the purpose of providing sufficient proof to the case file. In this milieu, given the high risks involved during the investigation, as well as after its completion, the undercover agent can act upon fictitious identity. This measure can be maintained during the evidentiary phase of the trial. Similarly, given the latent threat that the undercover agent suffers by its inclusion in criminal organizations, as well as the need for his inclusion in future covert actions it is crucial that his participation as a witness in the trial is properly shielded. Thus, when the undercover agent provides, exceptionally, statements in the trial, he shall do so always through videoconference with voice and image distortion. This measure can guarantee the anonymity of the undercover agent and concomitantly, that the adversarial principle and the right of the accused to a fair trial is not prejudiced since, in those circumstances, the diligence will be supervised in its entirety (in the audience and with the undercover agent) by a judge.